Transforming growth factor‐β1 signalling triggers vascular endothelial growth factor resistance and monocyte dysfunction in type 2 diabetes mellitus. Issue 11 (4th May 2021) - Makowski, Lena‐Maria; Leffers, Merle; Waltenberger, Johannes; Pardali, Evangelia
Abstract: Type 2 diabetes mellitus (T2DM) leads to monocyte dysfunction associated with atherogenesis and defective arteriogenesis. Transforming growth factor (TGF)‐β1, placenta growth factor (PlGF)‐1 and vascular endothelial growth factor (VEGF)A play important roles in atherogenesis and arteriogenesis. VEGF‐receptor (VEGFR)‐mediated monocyte migration is inhibited in T2DM (VEGFA resistance), while TGF‐β1‐induced monocyte migration is fully functional. Therefore, we hypothesize that TGF‐β antagonises the VEGFA responses in human monocytes. We demonstrate that monocytes from T2DM patients have an increased migratory response towards low concentrations of TGF‐β1, while PlGF‐1/VEGFA responses are mitigated. Mechanistically, this is due to increased expression of type II TGF‐β receptor in monocytes under high‐glucose conditions and increased expression of soluble (s)VEGFR1, which is known to interfere with VEGFA signalling. VEGFA resistance in monocytes from T2DM patients can be rescued by either experimental down‐regulation of TGF‐β receptor expression in vitro or by functional blocking of TGF‐β signalling using either a TGF‐β receptor kinase inhibitor or a TGF‐β neutralizing antibody. Our data demonstrate that both T2DM and high‐glucose potentiate the TGF‐β pathway. TGF‐β signalling impairs VEGFR‐mediated responses in T2DM monocytes and in this way contributes to mononuclear cell dysfunction, provide novel insights into T2DM vascular dysfunction.